Flora of the Guianas. - Ahti, Teuvo, 1934-; Sipman, H. J. M. (Flora of the Guianas, Series E, Fungi and lichens ;, 2013)
A critical, illustrated look at the flora of Guyana, Suriname, and French Guiana, designed to treat phanerogams as well as cryptogams of the area. This edition covers the Cladoniaceae family, and provides plant descriptions, distribution, and taxonomic keys.